3D Model Reconstruction of Rocks on a Slope for Simulating a Rock Fall - Kitahra, I.; Atsumi, S.; Degawa, R.; Kawamura, Y.; Jang, Hyong Doo; Ohia, Y. (American Society of Civil Engineers, 2016)
Abstract: For reducing damage of rock fall, it is important to estimate the route, leap height and velocity of the rock. Although research about estimation of falling motion of rocks are actively conducted, there are still unsolved issues, since rock fall is a complex phenomenon affected by position, size, or shape of rocks and angle of slope. This paper proposes a method of rock fall simulation using a 3D model of rock and slope reconstructed by merging multiple-view images. The proposed method requires only a mobile camera to generate a 3D model, so that more practical rock fall simulation can be realized. In addition, reconstructing textured 3D model makes inspectors visually confirm how the rock falls on the slope. Due to the difficulty capturing multiple images of both of rocks and a slope at a same time, rocks and a slope are individually captured, and then, they are merged in the post process. There are two problems to be solved for merging them accurately. One is the significant difference in their spatial resolution; the other is the difference in the appearance caused by perspective projection. We conduct an experiments using multiple images of rocks and slopes captured at actual landslide site.